Potensi Senyawa Alami dalam Polifenol dengan Mekanismenya untuk Melawan Kanker - Mesensy, Natasya; Putri, Giska Tri (Medula, 2024)
Globally, cancer is the leading cause of death because its pathophysiology includes multifactorial components. In general, various things mediate its development, such as genetic mutations, toxin intake, radiation exposure, unhealthy food, and work pressure. To increase the chance of cure from cancer and the possibility of survival, early detection, and appropriate treatment are needed. In the last decade, the high content of bioactive compounds contained in nutraceutical components has been considered as a complement in food, food supplements, and medicines. The medicines here include appropriate treatment to fight cancer without worrying about anticancer side effects that can cause adverse responses. Compounds in nutraceuticals are natural bioactive ingredients that have anticancer properties, which can kill cells that have metastasized or have become cancerous without being toxic to surrounding normal cells. This effect is proven when these natural bioactive compounds are contained in conventional medicine and show that nutraceutical supplementation contributes to the success of cancer treatment as an anticancer. This review examines the current knowledge from various literature regarding several natural bioactive extracts that contain certain polyphenolic compounds. The activity of this compound can be seen from the inhibition of cell proliferation, anti-inflammatory action, and antioxidant activity. Therefore, nutraceutical supplementation can be recommended along with conventional treatment to obtain a better therapeutic response in cancer patients.